Occupational outcomes of people with multiple sclerosis: a scoping review - Guglielmo Dini; Alfredo Montecucco; Nicoletta Debarbieri; Paolo Durando; Giuliana Buresti; Benedetta Persechino; Matilde Inglese; Bruno Kusznir Vitturi; Alborz Rahmani; Elvira Sbragia; Paolo Bandiera; Michela Ponzio; et al. (BMJ Open)
Objectives To update the knowledge on the occupational outcomes associated with multiple sclerosis (MS), systematically examine the extent, scope and nature of the pre-existing literature and identify research gaps in the existing literature.Design Scoping review.Data sources A comprehensive database search of PubMed/MEDLINE, Scopus, SciVerse ScienceDirect and Web of Science was performed. There were no time limits.Eligibility criteria We included any peer-reviewed original article reporting the occupational outcomes of people with MS between the ages of 18 and 65 years. We excluded those off-topic and with insufficient information.Methods This review was conducted following the Joanna Briggs Institute recommendations and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for scoping review checklist. Screening, reading of full-texts and data extraction was performed in a standardised way by expert reviewers from 14 July 2021 to 31 October 2021. We provided a narrative synthesis and an overview of findings.Results The initial systematic search yielded 104 228 results. After removing duplicates and applying the exclusion criteria, 403 articles were included in the review. In total, the studies evaluated 492 062 subjects with MS. One hundred fifty-four (38.2%) articles were published in the last 5 years, mostly from Europe and North America (50.9% and 33.0%, respectively). Concerning the occupational outcomes, studies mostly addressed unemployment (311, 77.2%), early retirement (120, 29.8%), disability pension (117, 29.0%), sick leave (77, 19.1%), the indirect cost of MS (74, 18.4%) and work characteristics (57, 14.1%). The results were categorised into seven subtopics: ‘Changes in work and occupational status due to MS’, ‘work-related socio-economic consequences of MS’, ‘risk factors for unfavourable occupational outcomes’, ‘reported barriers to employment’, ‘reported job accommodations and vocational rehabilitation strategies’, ‘job satisfaction, stigma, and disclosing the diagnosis in the workplace’ and ‘rating clinical scales’.Conclusions There are several issues that deserve further in-depth study by the scientific community in order to improve the occupational outcomes of people with MS.